Discursos jurídicos em crimes de homicídio contra mulheres, Formosa-GO - Cardoso, João Ederson Gomes (Universidade do Vale do Rio dos Sinos, 2021)
In this dissertation, I sought to demonstrate the conceptions of gender present in legal speeches in the Jury Court of the District of Formosa-GO, giving greater emphasis to the discourse of the defense. The documents were the corpus of the analysis and the method used was discourse analysis, aiming to answer the starting question, about the gender conventions in discourses in processes of competence of the Jury Tribunal of the County of Formosa-GO that involve the practice of murder of women. I analyze which gender values that circulate in society are inserted in legal discourses and which justifications are presented in favor of those who commit the crime, since the justifications have the purpose of convincing the jurors. Therefore, 4 (four) criminal cases of Jury Court competence were related, with the purpose of interpreting the legal discourses contained therein, thus making a relation with gender conceptions, in order to verify which values are present.
Keywords: Discurso; Convenções; Gênero; Júri; Processos; Discourse; Conventions; Gender; Jury; Lawsuits; ACCNPQ::Ciências Humanas::Sociologia